2017
DOI: 10.1088/1757-899x/191/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research to investigate the performance of bio coolant when turning of mild carbon steel

Abstract: Abstract. Some literatures have been reported that the using bio coolant show better lubricating and cooling performances and reduce the occupational health risks associated with petroleum-oil-based coolant since they have lower toxicity. This paper investigates the effect the cutting conditions on the surface roughness through turning of mild carbon steel using dry, coolant and bio coolant. Measurement of surface roughness was conducted and then compared with the change of the cutting conditions. The relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In this experiment, it can be obtained for other responses such as power consumption [14][15], and energy consumption [16][17].…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, it can be obtained for other responses such as power consumption [14][15], and energy consumption [16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Nur et al [13,14] also investigate the turning of AISI 316L stainless steel using coated carbide, they concluded that the equations prediction developed for machining output can be useful in determining the optimum cutting parameters. Another study was conducted by Nur et al for turning of aluminum alloys [15][16][17] and carbon steel [18][19]. The research result stated that the energy demand was influenced by cutting speed.…”
Section: Resultsmentioning
confidence: 99%